The use of zeolite as zearalenone adsorbent in the nutrition of calves - Ne?ic, S.; Grubic, G.; Adamovic, M.; ?or?evic, N.; Stojanovic, B.; Bo?i?kovi?, A. (Cuban Journal of Agricultural Science, 2010)
The experiment was aimed at studying the effect of the use of modified zeolite in the prevention of harmful influence of zearalenone on growth, biochemical, and hematological parameters of blood and the pH value of the rumen fluid in calves. It was performed on 60 Holstein calves, in five groups of 12 animals that were uniform in origin, age and body weight. There were six males and six females in each group. The treatments were the following: A ? no zearalenone and zeolite, B ? no zearalenone with 2 g kg-1 zeolite added in concentrate, C ? with zearalenone (3.36 mg kg-1 concentrate) and no zeolite added in concentrate, D ? with zearalenone (2.86 mg kg-1 concentrate) and 2 g kg-1 zeolite added in concentrate, E - with zearalenone (3.34 mg kg-1 concentrate) and 5 g kg-1 zeolite added in concentrate. It can be concluded that there was no significant effect of adding 0.2 and 0.5 % of modified zeolite in concentrates for weaned calves, with or without presence of zearalenone (intake 5.29 - 6.22 mg d-1) on production performances of calves, as well as on biochemical and hematological parameters of the blood. Zeolite significantly positive affect ruminal pH, which confirms the using of this mycotoxin adsorbent as buffering agent. The presence of zearalenone, with the exception of the tendency to decrease average daily gain, did not significantly affect production performances and recorded physiological parameters of weaned calves. It cannot be accurately concluded about detoxifying effect of modified zeolite, because of the lack of significant zearalenone negative effect. Key words: mycotoxin, adsorbent, daily gain, pH value.